Disseminated peritoneal cystic Echinococcosis in a patient with HIV: case report. - Ruiz Pérez, P.J. (2023)
Cystic echinococcosis is a zoonotic infection caused by the larva of Echinococcus granulosus, which is capable of invading several organs starting from the human intestine. There are several complications in cases of co-infection with the human immunodeficiency virus (HIV), which are conditioned by the immunosuppressive disease and have poor prognosis. This report aims to describe a case of multi-cystic peritoneal echinococcosis in a patient under antiviral treatment for HIV for almost ten years, who received albendazole, underwent surgery and progressed favorably. This would be the first Peruvian report of a person with HIV and cystic echinococcosis.